Retained blood syndrome after cardiac surgery: review - Niemann, Bernd; Grieshaber, Philippe (European journal of cardio-thoracic surgery, 2025)
OBJECTIVES: Retained blood syndrome (RBS) is defined as the postoperative retention of blood within the thoracic cavity. In addition to the mechanical impacts on cardiac and pulmonary function, RBS triggers inflammatory processes. It is associated with increased morbidity following cardiac surgery. The goal of this non-systematic review was to summarize the current understanding of the pathophysiology, consequences and both prophylactic and therapeutic measures related to RBS. - METHODS: The subjects to be covered were defined in advance. A literature search was conducted in PubMed and Google Scholar using relevant search terms and MeSH terms. - CONCLUSIONS: RBS is a significant complication following cardiac surgical procedures. It is associated with a poorer prognosis due to mechanical suppression of haemodynamics and the amplification of inflammatory processes. Therefore, preventing pericardial and pleural effusions should be a priority in cardiac surgical care. If RBS occurs, aggressive anti-inflammatory therapy should be initiated to prevent the development of long-term complications.